SELEMBAYUNG SEBAGAI IDENTITAS KOTA PEKANBARU: KAJIAN LANGGAM ARSITEKTUR MELAYU - Dimas Wihardyanto, Gun Faisal, (Indonesian Journal of Conservation, 2013)
Pekanbaru, like other cities in Indonesia experienced the turmoil of physical development which in turn raises the question of what exactly can be appointed as the physical identity of the results of development that occurs. Traditional architecture reuse or constituent elements of traditional architecture is considered to be the fastest way to get the identity of the building and the city. However, no thorough understanding of the traditional architecture led to a blurring or loss of significance of the use of the elements of the traditional architecture, and often traditional architectural elements are placed not in the proper place. Selembayung as elements of traditional Malay architecture which was adopted as the identity of the building and the city of Pekanbaru was experiencing a shift in meaning due to the lack of a thorough understanding of traditional Malay architecture. Thus, in applying it tends to be treated as a patch that is sometimes incorrect placement.Keywords : Pekanbaru , Traditional Malay Architecture , Building Identity , Identity Cities ÃÂ Pekanbaru, seperti layaknya kota-kota lain di Indonesia mengalami gejolak pembangunan fisik yang pada akhirnya menimbulkan pertanyaan apakah sebenarnya yang bisa diangkat sebagai identitas fisik dari hasil-hasil pembangunan yang terjadi. Menggunakan kembali arsitektur tradisional ataupun elemen-elemen penyusun arsitektur tradisional tersebut dipandang menjadi cara tercepat guna mendapatkan identitas bangunan maupun kota. Namun demikian pemahaman yang tidak menyeluruh dari arsitektur tradisional tersebut menyebabkan kaburnya atau hilangnya makna dari penggunaan elemen-elemen arsitektur tradisional tersebut, bahkan seringkali elemen-elemen arsitektur tradisional ditempatkan bukan pada tempat yang seharusnya. Selembayung sebagai elemen arsitektur tradisional Melayu yang diangkat sebagai identitas bangunan dan Kota Pekanbaru ternyata mengalami pergeseran makna akibat tidak adanya pemahaman yang menyeluruh terhadap arsitektur tradisional Melayu. Sehingga dalam menerapkannya cenderung diperlakukan sebagai tempelan yang terkadang penempatannya salah. Kata Kunci: Pekanbaru, Arsitektur Tradisional Melayu, Identitas Bangunan, Identitas Kota ÃÂ